2009
DOI: 10.3233/ch-2009-1223
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound in liver transplant: First results and potential for complications in the postoperative period

Abstract: Purpose: This study compared the efficacy of contrast-enhanced ultrasound (CEUS) using a second generation contrast medium versus CT or MRA in the assessment of vascular and biliary complications in postoperative follow-up of liver transplantation.Methods and materials: The study group consisted of 36 consecutive liver transplant recipients who underwent posttransplantation CEUS examination after developing ascites and/or unclear liver function tests. Real time CEUS was performed after a bolus injection of Son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Lack of visualization of the arterial tree, expected to be seen before portal enhancement, indicates complete arterial thrombosis with very high positive predictive values [10,32,99,131]. Identification of the arterial branches when conventional Doppler has failed [131], may allow subsequent targeted Doppler reassessment, which is needed to distinguish thrombosis from slow flow caused by vasoconstriction or splenic steal from postthrombotic/stenotic recanalization, tasks not achievable using CEUS alone.…”
Section: Image Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of visualization of the arterial tree, expected to be seen before portal enhancement, indicates complete arterial thrombosis with very high positive predictive values [10,32,99,131]. Identification of the arterial branches when conventional Doppler has failed [131], may allow subsequent targeted Doppler reassessment, which is needed to distinguish thrombosis from slow flow caused by vasoconstriction or splenic steal from postthrombotic/stenotic recanalization, tasks not achievable using CEUS alone.…”
Section: Image Interpretationmentioning
confidence: 99%
“…Before liver transplantation, CEUS is indicated to assess portal vein thrombosis and characterize focal liver lesions in cirrhosis. After liver transplantation, CEUS can be performed at the bedside or in the intensive care unit, avoiding most of the risks associated with CECT or angiography [10,32,63,100,154]. CEUS is indicated for:…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also demonstrated the potential advantage of GLCM analyses to evaluate vascular damage in resource‐challenged settings where contrast enhancement may not be available. This study adds to the repertoire of some recent studies where vascular anatomy has been assessed after liver transplantation. Our study correlates the ultrasound imaging with the molecular changes during ex vivo storage of livers for the first time.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, the morphological changes in the contrast‐enhanced blood signal beam are considered the critical factors for distinguishing stenosis from SASS 23. Recently, CEUS has been widely used to detect hepatic artery stenosis and thrombosis as well as complications of bile ducts 23, 24. To our knowledge, this is the first investigation devoted to the use of CEUS for the diagnosis of SASS.…”
Section: Discussionmentioning
confidence: 98%